2-Dimensional Animation: The After-Effect of Perak’s War - Kamarudin, Muhammad Faiq Adam; Jaafar, Roslinawati (Journal of Computing Technologies and Creative Content, 2021)
Although most of us are familiar with the impact of the Pangkor Treaty and the the appointment of J. W. W. Birch as the first British resident in Tanah Melayu. It was a marking point of intervention between the British in the administration of Malay states. Unfortunately, the basis which lean more towards oppression that was introduced by Birch inflict angers which lead to the death of Birch in Pasir Salak and triggers the Perak War. After the tragic event, many were sentences to death. Sultan Abdullah dan a few other Malay officials were thrown to Seychelles Island. Younger generation as of today, the lack of knowledge on the topic of history is quite a concern. The aim of this research is to teach the younger generation about the life of Sultan Abdullah after the tragedy of the Perak War in the style of 2D animation storytelling. 2-Dimensional animation was chosen as it’s a more convenient and easier way in educating especially the younger people on the importance of history. The 2-Dimentional animation will help in understanding more of the story. The commodity chosen for this project is the 3P model consisting of pre-production, production, and post-production.